Afrocantharellus gen. stat. nov. is part of a rich diversity of African Cantharellaceae - D.D. Tibuhwa; S. Savić; L. Tibell; A.K. Kivaisi (IMA Fungus)
A new genus in the Cantharellaceae, Afrocantharellus, is recognized based on results from phylogenetic analyses of rDNA LSU and concatenated LSU/5.8-ITS2/ATP6 data. It was previously recognized as a subgenus, but comprehensive fieldwork and the acquisition of numerous sequences for previously neglected African Cantharellus species formed the basis for a reappraisal of generic and species delimitations. Afrocantharellus is characterized morphologically by the basidiomes having thick, distantly spaced diverging folds of variegated colour. In contrast to most of Cantharellus, Afrocantharellus mostly lacks clamp connections. Phylogenies of Cantharellus and Afrocantharellus based on LSU and a concatenated data set are provided, along with descriptions of and a key to the four species and one form of Afrocantharellus recognized. Six new combinations are made.